2014
DOI: 10.1074/jbc.m114.592295
|View full text |Cite
|
Sign up to set email alerts
|

RING Finger Protein RNF207, a Novel Regulator of Cardiac Excitation

Abstract: Background: A genetic variant within RNF207 is associated with a prolonged QT interval. QT interval prolongation may lead to arrhythmia, a risk factor for sudden cardiac death. Results: RNF207 regulates action potential duration and the repolarizing channel HERG. Conclusion: RNF207 is an important regulator of cardiac excitation. Significance: Understanding the composition and dynamics of membrane complexes is important in unraveling the mechanism of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…Consistent with our results, the results of microarray analyses available from the NCBI public functional genomics data repository [21,61] showed that the mRNA level of Rnf207 is significantly reduced in NRCs treated with the pyridine activator of myocyte hypertrophy, which induces cardiac hypertrophy [62], and in mouse hearts treated with isoproterenol, which causes tachycardia-induced HF [63].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our results, the results of microarray analyses available from the NCBI public functional genomics data repository [21,61] showed that the mRNA level of Rnf207 is significantly reduced in NRCs treated with the pyridine activator of myocyte hypertrophy, which induces cardiac hypertrophy [62], and in mouse hearts treated with isoproterenol, which causes tachycardia-induced HF [63].…”
Section: Discussionsupporting
confidence: 91%
“…However, the precise molecular mechanism by which RNF207 affected the energy metabolism in isolated cardiomyocytes is not clear. Recent studies have shown that genetic variation in RNF207 is associated with prolongation of the QT interval [52,53] and that RNF207 knockdown in zebrafish embryos prolonged the action potential duration (APD) [21]. It was also reported that VDAC1 is the only identified protein mediating Ca 2+ transport in the outer mitochondrial membrane [54] and that Ca 2+ dynamics is important not only for APD [55,56] but also for the regulation of cellular energetic production [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions, GWAS-identified loci that were not previously linked to cardiac electric function are yet untapped for gene identification and mechanistic insight. [182][183][184] In conducting functional studies on genes from GWAS loci (Figure 7), many considerations should be taken into account at the outset. Rather than a specific variant, GWAS illuminates a haplotype and any SNP on that haplotype that is in linkage disequilibrium with the lead-SNP from GWAS could in theory mediate the observed effect ( Figure 7B).…”
Section: Gwas On Ecg and Cardiac Structure And Function Parametersmentioning
confidence: 99%
“…9 In addition, RNF207 is also indirectly correlated to cardiac death via its interaction with QT interval prolongation, the main cause of arrhythmia. 10 RNF182, a cytoplasmic protein with low abundance, is predominantly expressed in the brain with amplified expression in postmortem Alzheimer's disease brain tissue, and its gene can be stimulated in cultured neurons subjected to cell death induced injuries. 11 Mammalian target of rapamycin (mTOR), as an atypical serine/threonine protein kinase, is the phosphoinositide 3-kinase (PI3K)-related kinase family and forms two kinds of different complexes named mTORC1 and mTORC2.…”
Section: Introductionmentioning
confidence: 99%